ANALISIS PENGARUH PROMOSI, LOKASI, PELAYANAN DAN SUKU BUNGA TERHADAP KEPUTUSAN PENGAMBILAN PEMBIAYAAN KREDIT USAHA RAKYAT (KUR) (Studi Pada Nasabah Bank BRI Desa Jaya Makmur Kecamatan Labangka) - Roos Nana Sucihati; S Suprianto; Dedi Mustiadi (Jurnal Ekonomi & Bisnis, 2020)
The purpose of this study was to know the effect of promotion, location, service and interest rates toward KUR financing decisions for customers of BRI Bank Jaya Makmur village, Labangka Sub-District. Type of this study was associative. The sample was determined using probability simple random sampling technique with a lottery technique so that the selected sample was 70 respondents from 240 customer of BRI. The data analysis technique used was multiple linear regression analysis, statistical test of t and F and test the coefficient of determination (R2). Based on the results of the study showed that partially the promotion and location variables had not effect toward the decision of KUR financing taking at BRI, while the service and interest rate variables had effect toward the decision of KUR financing taking at BRI Bank customers of Jaya Makmur village, Labangka Sub-District. Simultaneously, the variable of promotion, location, service and interest rates had effect toward the decision of making KUR financing for customers of BRI Bank Jaya Makmur village, Labangka Sub- District. The ability of the independent variable to influence the dependent variable was of 64.1%, while its remaining of 35.9% was influenced by other variables outside the study.